Endophthalmitis due to caterpillar setae: surgical removal and electron microscopic appearances of the setae. Issue 4 (April 1984) - Steele, C; Lucas, D R; Ridgway, A E
Abstract : A case of endophthalmitis due to caterpillar setae was, for the first time, successfully treated by surgical removal of the setae. The procedure was facilitated by the use of sodium hyaluronidate. Scanning and transmission electron microscopy of the setae showed evidence of enzymatic degradation of the shaft and burial of the spines in exudate.